2011
DOI: 10.1080/09064710.2010.491954
|View full text |Cite
|
Sign up to set email alerts
|

Improving agricultural water use efficiency by nutrient management in crop plants

Abstract: Improvement of agricultural water use efficiency is of major concern with drought problems being one of the most important factors limiting grain production worldwide. Effective management of water for crop production in water-scarce areas requires efficient approaches. Increasing crop water use efficiency and drought tolerance by genetic improvement and physiological regulation may be a means to achieve efficient and effective use of water. A limited water supply inhibits the photosynthesis of plants, causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 91 publications
4
116
0
2
Order By: Relevance
“…It has been reported that Si causes an improvement of water use efficiency and stimulation of antioxidative defense system in winter wheat (Liang et al, 2008), Paspalum vaginatum (He et al, 2010) and cucumber leaves (Liu et al 2009). Increase in production of antioxidants and decline of ROS generation mediated by Si causes reduction of photo-oxidative damage, maintenance of chloroplast membranes integrity and thus enhancement of plants stress tolerance (Liang et al, 2008;Waraich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Si causes an improvement of water use efficiency and stimulation of antioxidative defense system in winter wheat (Liang et al, 2008), Paspalum vaginatum (He et al, 2010) and cucumber leaves (Liu et al 2009). Increase in production of antioxidants and decline of ROS generation mediated by Si causes reduction of photo-oxidative damage, maintenance of chloroplast membranes integrity and thus enhancement of plants stress tolerance (Liang et al, 2008;Waraich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For Sahelian conditions, Sivakumar and Salaam (1999) reported a 84 % increase of water use efficiency in millet (WUE, grain yield per mm rain), of which TE is an important component, due to the addition of mineral fertilizers. Therefore, under limited water supply, plant nutrients may play an important role in enhancing WUE (Waraich et al 2011), and more research is required to understand genotypic differences in TE under various levels of P.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the effect of irrigation water, N or P was closely related to the ability of potato plant to utilize them from the soil. Waraich et al (2011) reported that when water inside the plant declines below a threshold level, stomata close and decrease transpiration rate resulting in reduction in water transport through the plant, consequently affecting roots ability to absorb water and nutrients as effectively as supposed to be done under normal transpiration. Therefore, it is possible that normal transpiration required certain amounts of irrigation water below which the high N or P rates cannot lead to greater potato growth and development.…”
Section: Discussionmentioning
confidence: 99%